2017
DOI: 10.1016/j.ejps.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Activation of GPER ameliorates experimental pulmonary hypertension in male rats

Abstract: Rationale Pulmonary hypertension (PH) is characterized by pulmonary vascular remodeling that leads to pulmonary congestion, uncompensated right-ventricle (RV) failure, and premature death. Preclinical studies have demonstrated that the G protein-coupled estrogen receptor (GPER) is cardioprotective in male rats and that its activation elicits vascular relaxation in rats of either sex. Objectives To study the effects of GPER on the cardiopulmonary system by the administration of its selective agonist G1 in mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 67 publications
5
35
0
Order By: Relevance
“…Changes in the PA artery flow profile might be related to the severity of PH, mainly when a triangular flow and a mid-systolic notching are observed [ 22 ]. Two weeks after MCT or saline administration, echocardiographic evaluation showed evidence of PH in the MCT-treated rats, including a change in the shape of the PA waveform ( Fig 1 ) in accordance with previous reports [ 21 , 22 ]. After the echocardiographic examination, the MCT-treated rats were divided into six treatment groups (n = 6 per group): 1.…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…Changes in the PA artery flow profile might be related to the severity of PH, mainly when a triangular flow and a mid-systolic notching are observed [ 22 ]. Two weeks after MCT or saline administration, echocardiographic evaluation showed evidence of PH in the MCT-treated rats, including a change in the shape of the PA waveform ( Fig 1 ) in accordance with previous reports [ 21 , 22 ]. After the echocardiographic examination, the MCT-treated rats were divided into six treatment groups (n = 6 per group): 1.…”
Section: Methodssupporting
confidence: 91%
“…Rats in the MCT group were given a single i.p. injection of MCT at 60 mgkg -1 body weight to induce PH using previously published methods [ 9 , 11 , 20 , 21 ]. Rats in the C group were injected with the same volume of sterile saline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, G1 did not seem a direct target for pulmonary vascular system diseases. However, it was demonstrated that prophylactic G1 treatment reduced the pulmonary hypertension (PH)-induced right ventricle dysfunction, it can be the results of G1-dependent releasing of nitric oxide [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac and vascular protection of E2 has been linked to the activation of GPER located on the cell membrane [109]. More importantly, the activation of GPER reverses PH-related cardiopulmonary dysfunction and exercise intolerance in both male and female MCT-PH rats [110,111]. In this regard, 2ME binds the membrane GPER and, via GPER-mediated transactivation of EGFR and ERK1/2 phosphorylation, downregulates AT1 receptor expression [90,91].…”
Section: Other Effects Of the 2-methylation Pathway Relevant To Pahmentioning
confidence: 99%